Local Wisdom and Food Security Among Rocky Land Farmers in Burangasi Village, South Buton Regency - La Janu; La Ino; Akhmad Marhadi; Syahrun; Wa Ode Winesty Sofyani (Lembaga Bale Literasi, 2026)
This study attempts to examine the concept of local wisdom and food security among farmers who are practicing farming rocky lands in Burangasi Village in Lapandewa District, South Buton Regency. The data collection method used was ethnographic wherein data was gathered by employing the participant observation method and in-depth interviews. Data obtained were then measured in qualitative descriptive measures. The results indicate that the farmers at Burangasi Village are not pessimistic of the constraints of their lands. Rather, they proactively take these limits as a challenge by realizing local wisdom of the ancestors. This acquired knowledge acts as a type of intangible capital and helps farmers in overcoming land-related issues and being adjusted to the natural environment around them. There are a number of land-use strategies designed to suit plant traits among them being growing on rock surfaces, rock cavities as well as in between rocks and rocky soil. Consequently, there is not a single piece of idle land. Farmers implement different adaptive measures in order to increase food security. These involve controlling planting systems with crop diversification (polyculture), specifically of staple foods; planting one crop on multiple plots; staggered and continuous harvesting systems; and preservation of harvested products by processing it into various products to lengthen the shelf life and prevent.